2008
DOI: 10.1080/02701367.2008.10599517
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Teachers' Perceptions of the Impact of Barriers to Teaching Physical Education on the Quality of Physical Education Programs

Abstract: A major aim of the current study was to determine what classroom teachers perceived to be the greatest barriers affecting their capacity to deliver successful physical education (PE) programs. An additional aim was to examine the impact of these barriers on the type and quality of PE programs delivered. This study applied a mixed-mode design involving data source triangulation using semistructured interviews with classroom teachers (n = 31) and teacher-completed questionnaires (n = 189) from a random sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
163
4
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(177 citation statements)
references
References 13 publications
7
163
4
3
Order By: Relevance
“…Thus, our results can be attributed to the physical activity component of the intervention, which included (i) the rearrangement of the classroom in order to assist the children to be more active, (Yasmeen et al) . Many teachers lack the skill to teach physical education efficiently (Morgan & Hansen, 2008). It is necessary for teachers to understand the process of developing motor skills and abilities, their importance and ways of teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results can be attributed to the physical activity component of the intervention, which included (i) the rearrangement of the classroom in order to assist the children to be more active, (Yasmeen et al) . Many teachers lack the skill to teach physical education efficiently (Morgan & Hansen, 2008). It is necessary for teachers to understand the process of developing motor skills and abilities, their importance and ways of teaching.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether teachers will have to assess and report student achievement against FMS proficiency. Current practice would suggest this is unlikely 10 but, given the evidence, this is what we should be striving for.…”
mentioning
confidence: 99%
“…However, this is cautioned by available evidence that shows there is strong and consistent consensus that generalist classroom teachers lack confidence to teach physical education, feel inadequately trained and prepared and tend to place physical education as a lower priority in an already 'crowded' curriculum. 9,10 There is also an immediate opportunity with the development of the Australian National HPE curriculum for primary and high schools to place opportunities to develop FMS centre stage in HPE programs. The public consultation phase for the Draft HPE curriculum has recently closed and it is currently being revised for publication in late 2013.…”
mentioning
confidence: 99%
“…In a study among primary school teachers, it was found that many were unable to fit in the mandatory hours across all subject areas, with most participants admitting that PE was the first to suffer (Morgan & Hansen, 2008a, 2008b. There is a range of other factors impacting on teachers, these include their lack of confidence to teach PE, a lack of time, poor facilities, inadequate resources and low levels of interest in PE in general.…”
Section: Primary School Context In New South Walesmentioning
confidence: 99%